How provincial governments respond to fiscal shocks and federal transfers - Ferede, Ergete; Dahlby, Bev (My University, 2023)
In this study, we investigate how Canadian provincial governments have responded to fiscal shocks, including changes in federal transfers, based on annual data spanning over half a century. We find that provincial governments have responded to a $1.00 increase in their per-capita budget deficits by cutting program spending by $0.18 and increasing own-source revenues by $0.09 the following year. As these responses only partially offset the deficit, provincial debt levels increase, and debt service costs rise. Thus, provinces that face adverse fiscal shocks and/or rising budget deficits in a given period inevitably respond by reducing program spending and/or hiking own-source revenues in future periods. This undermines the arguments advanced by some politicians and policy analysts who believe provinces can run ongoing deficits without having to “face the fiscal music” in the future.
Keywords: provincial governments; fiscal shocks; budget deficits